Instrumentos de queda livre para medição de parâmetros oceanográficos - Ribeiro, Carlos Eduardo Parente (1977)
This work deals with the development of free falling oceanographic instruments. The stability and constant speed during the fall are guaranteed by the action of rotary wings attached to a cilindric body. Signals from the sensors are brought aboard by electrical cable where they feed graphic or magnetic recorders. One can get profiles from the different parameters versus time which represents depth due to the constant falling speed. Among the principal characteristics of these instruments are the high rate of data acquisition, low cost, ease of handling and the possible use of single or multiple sensors. The development of the free falling body is presented followed by the adaptation of temperature, spectral irradiance and transmittance sensors to this body.